Archaeoarchitecture. Contribution of the discipline of architecture to the study of archaeological monuments - Carella, Alfio Pinasco (2019)
Ancient architectural monuments stand witness to the needs of its builders and its eras.The study of these buildings brings us closer to understanding the priorities of their cultural values and their technical and artistic achievements, which are valuable andstill relevant in modern architecture. Inter and multidisciplinary research work carriedout during these years has enriched the methodology for archaeoarchitecturalstudy, thanks to each researcher’s particular focus. In this contribution I describe mymethodology proposal for the study of Archaeoarchitecture and its contributions,conceived as an architectural specialisation, related to the record, study anddissemination of the cultural values of archaeological buildings. I discuss newmeasuring data collection and analysis instruments, that allow for more accurate, fastand efficient studies of design patterns, geographical and astronomical alignmentsin extensive monumental complexes.